Formação de professores para a educação infantil bilíngue - Wolffowitz-Sanchez, Norma (2009)
The objective of this research is to investigate how Teachers Development for the Early Bilingual Education occurred based on the production of collaborative spaces aimed at sharing of meanings and the production of new senses on Early Bilingual Education. The study is based on the Socio‐Historical‐ Cultural Activity Theory according to Vygotsky (1930/2003, 1930/2000, 1934/2001), Leontiev (1977, 1978) and Engeström (1987, 1999). It is also based on the vygotskian conception of teaching‐learning and bakhtinian dialogism and verbal interaction (Bakhtin and his Circle 1979/2000, 1929/2002). It is possible to understand the roles of teacher‐trainer and student‐teachers in the activity of Teachers Development for the Early Bilingual Education based on this theoretical framework because all human activity is mediated by cultural artifacts socio‐historically situated, and these artifacts are produced and transformed by the socio‐historical‐cultural subjects and, in turn, transform the subjects. From this perspective, the relationship of humans with their peers and the world is dialectical and language is the mediator of verbal interactions. When humans share meanings from the senses, they bring to the interaction the various voices that constitute them and the various voices of others (Bakhtin and his Circle, 1929/2002). The activity of production of shared meanings is not free of tensions and confrontation and they allow reconstruction and transformation of knowledge on a creative and expansive cycle (Engeström, 1987). This is a critical‐collaborative research (Magalhães 2002, 2004, 2005, 1990/2006, 1992a/2006, 1992b/2006, 1996/2006, 1998a/2006e, 1998b/2006; Liberali, 2007a, 2007b, 2006, 2004). This study was conducted in LAEL / PUC‐SP and in a preschool in the city of São Paulo, with one teacher‐trainer and three student‐teachers who are members of LACE Research Group. The research was conducted in the academic year of 2008 and the data analyzed correspond to the first academic semester. The data were produced and collected during reflexive sessions, sessions of study and lesson planning, exchange of emails, reports, audio and video classes. The analysis of selected data observed the roles of each participant throughout the training, and collaborative spaces for the production of knowledge between teacher‐trainer and student‐teachers in development, and also if these spaces contributed to the production of knowledge for Early Bilingual Education. The results of the first academic semester showed that there was production of knowledge for Early Bilingual Education due to the creative and collaborative spaces. Besides student‐teachers participants, after being in the activity for some time, started to assume more central roles and fulfilled more responsibilities and tasks, so that the teacher‐trainer moved from the central participation to the periphery of the activity. Participants of this activity of teacher education project called Learn Play: Bilingual Education have emancipated at all times through the present tension and conflict in the negotiation of senses and meanings that expanded the activity. This teacher education project was critical, creative and collaborative in that together the participants could go beyond themselves